Internet accuracy of publicly available images of meniscal tears - DeFroda, Steven F.; Milner, John D.; Bokshan, Steven L.; Owens, Brett D. (The Physician and sportsmedicine, 2018)
Background: The Internet is an easily accessible resource for both providers and patients. Despite this, the Internet is not peer reviewed, leaving Internet searches subject to inaccuracies, especially with regards to medical information. The purpose of this study was to review Internet images of meniscus tears using three popular search engines: Google, Bing, and Yahoo. Methods: A search query was performed on the aforementioned search engines for the term: 'meniscus tear'. The first 100 images found for each individual search were analyzed by two independent reviewers with different levels of orthopedic training (orthopedic surgery resident and medical student). Inter-rate reliability and accuracy was determined for each of the search engines. The images were defined based on the source that published the image as either educational (published by hospital or medical association), commercial (published by a device company), or individual (published via a physician). Results: The inter-rater reliability was excellent (Cronbach's alpha = 0.91), (Cronbach's alpha = 0.94), (Cronbach's alpha >0.90) on Google, Bing, and Yahoo, respectively. When comparing the search engines for correctness, Google had 82% accuracy, compared to 81% for Bing and Yahoo. All three search engines have a similar mix of source material with educational images consisting of 86% of Google images, 84% for Yahoo, and 89% for Bing. Conclusion: Our study revealed that the three search engines queried displayed meniscal tear images with >80% accuracy when evaluated by two independent reviewers. Despite this, many images may still be seen as highly technical, or esoteric to an untrained individual. Ultimately, physicians should take an active role in making high quality, easy to understand medical resources, and anatomic diagrams available to their patients to avoid confusion and enhance understanding.